Comments on the discordant recommendations for the use of symptomatic slow-acting drugs in knee osteoarthritis. (May 2015) - Reginster, Jean-Yves; Cooper, Cyrus; Hochberg, Marc; Pelletier, Jean-Pierre; Rizzoli, René; Kanis, John; Abadie, Eric; Maheu, Emmanuel; Brandi, Maria Luisa; Devogelaer, Jean-Pierre; Branco, Jaime; Herrero-Beaumont, Gabriel; et al.
Abstract Despite the near concurrent publication by influential scientific organizations, there are important differences in interpretation of the evidence base and the conclusions derived from the recent Osteoarthritis Research Society International (OARSI) guidelines for the management of knee osteoarthritis, the American College of Rheumatology (ACR) guidelines (concerning also hip and hand osteoarthritis) and the algorithm recommendations by the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO). This is particularly evident for the drug class of symptomatic slow-acting drugs in osteoarthritis. In this paper, we highlight these differences and try to understand where they derive from, proposing an evidence-based interpretation.